(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the theoretical foundations of implementing scientific research results into practice, existing institutional challenges, and innovative mechanisms for overcoming them. Based on the experience of Uzbekistan and international scientific approaches, the relevance of the “science – industry – government” integration is substantiated. The study develops systematic proposals relying on legal and regulatory documents, academic sources, and modern innovation models.